Quality of Life: Information and Learning Resources in Supporting People with Severe Life-Changing Injuries to Return to Independence - Bernadette Cassidy; Alan Clarke; Said Shahtahmasebi (The Scientific World Journal)
This paper reports the first stages of the development of an integrated care model for people with massive sudden change in their lives with special reference to spinal cord injuries. The model aims to be holistic by placing the patient at the centre of the service. In addition to providing medical care for physical injuries, the model emphasises at the outset that regaining a good quality of life postinjury is expected. There is quality of life after change if individuals and their support network are provided with access to quality information and evidence for them to make informed choices. In New Zealand, this has been referred to as “life beyond bugger”!